A Partition Approach to Interpolate Polygon Sets for Animation - Ramos, Alexandre R. C.; Santos, Emanuele M.; Cavalcante-Neto, Joaquim (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI), 2019)
The use of animation can be a good alternative to static visualizations when communicating dynamic changes. Some approaches already represent spatiotemporal phenomena using a polygon set for each time instant. However, these representations are static and not general enough to be applied for the interpolation of arbitrary polygons. Furthermore, the problem of interpolating arbitrary polygons present a set of requirements that are not satisfied by the currently available tools. For example, the polygons are arbitrary and the interpolation should be smooth and fully automatic (not requiring user intervention). To solve this problem, we present an approach to interpolate arbitrary polygon sets that satisfy those requirements and that can be used to visualize temporal changes of different phenomena as an animation. In the proposed approach we apropriately subdivide and identify correspondences between origin and target polygon sets. Our approach is general enough so that different polygon subdivision techniques can be used. We also performed a series of experiments comparing a few different techniques and discuss the results.